A questão agrária e soberania alimentar: o caso do assentamento 8 de Junho em Laranjeiras do Sul - PR - Fabrício, Rosineide (2016)
This paper illustrates a study about Food Sovereignty analyzing the concrete experiences of the settlement on June 8 in the town of Laranjeiras do Sul, South Centre of Paraná State. This research brings a historical about the struggle for land in Brazil, played by poor peasants without land and with small lands. The choice of the method of historical and dialectical materialism allowed a deeper analysis of the Food Sovereignty in Brazil. Within a class design our country has historically been dominated and subjugated by the international division of labor, dictated by imperialist countries and submitted to the economy of these. Opposed to this logic and this productive agricultural model, producing for domestic consumption it is imperative for the attainment of food sovereignty. In this perspective we maintain that the effectiveness of any policy aimed at the Food sovereignty is only possible to break with the current agrarian export economic model, to which the country is undergoing. It is considered that it is in this question lies the perspective of food sovereignty, which can't be conceived in practical terms, out of a great project of social transformation. therefore the struggle to end the dominant landholder system in our country, the only way to ensure food sovereignty, shall necessarily be a struggle for economic and political sovereignty, breaking with the country's subjugation to the world order determined by world economic powers. Empirical research, at Settlement June 8, revealed that the confrontation, resistance and performance of farmers linked to the Landless Rural Workers Movement (MST) in the struggle to guarantee food sovereignty, has shown several advances. Although only the access to land by peasants is not the guarantee of food sovereignty is a basic criterion to ensure the material condition of the production of food for people living and working in the field, making it possible to create the conditions of autonomy in food production, as own consumption of communities without becoming prisoners of the market controlled by direct food trade monopolies for consumers. It is therefore to develop under the scientific theory of classism - Marxism - the forms of organization and peasant struggles in the destruction of the landlord system associated with the destruction of capitalism